The prototype design of the half-wave resonator at the Rare Isotope Science Project (RISP) - Park, Gunn-Tae; Hyun, Myungwook; Jung, Hoechun (Journal of the Korean Physical Society, 2015)
The progress in the prototype design of the half-wave resonator (HWR) at the Rare Isotope Science Project (RISP) is reported. The process is reaching its final stage, the complete engineering design. The RISP and the associated vendor, VITZRO tech, are ready to manufacture the prototype. In this paper, we describe the detailed design spanning the electromagnetic design, the multipaction, the error analysis, and the mechanical design, and we give the expected performance based on extensive simulations using 3D finite-element-analysis (FEA) codes